Epimedium koreanum Nakai-Induced Liver Injury-A Mechanistic Study Using Untargeted Metabolomics - Pin Li; Lin Zhang; Zhaojuan Guo; Qianjun Kang; Cong Chen; Xiaoyao Liu; Quantao Ma; Jingxuan Zhang; Yujie Hu; Ting Wang (Frontiers Media S.A., 2022)
Epimedii Folium is widely used worldwide as an herbal supplement, and the risk of its induced liver damage has emerged in recent years. Our preliminary study has found that, among several Epimedii Folium species specified in the Chinese Pharmacopoeia, Epimedium koreanum Nakai has a more severe propensity for hepatotoxicity. However, the mechanism of hepatotoxicity of Epimedium koreanum Nakai is still unclear. In this study, untargeted metabolomics was performed to analyze the serum and liver tissue to explore the mechanism of hepatotoxicity of Epimedium koreanum Nakai. The results of experiments in vivo showed that, after 28 days of exposure to Epimedium koreanum Nakai ethanol extract (EEE), the liver weight, levels of AST, ALP, TBIL, etc. in serum of rats in the EEE group were significantly increased, as well as severe cytoplasmic vacuolation appeared in the liver tissue, which suggested that EEE has significant hepatotoxicity. Subsequently, the results of metabolomics revealed significant changes in the metabolic profile in the liver and serum of rats after EEE exposure, in which metabolites in serum such as flavin mononucleotide, phenylacetylglycine, glutathione, l-tryptophan, and sphingomyelin were able to accurately identify liver injury caused by EEE and could be used as serum markers to reflect EEE-induced liver injury. The KEGG pathway enrichment analysis revealed that EEE caused extensive effects on rats' metabolic pathways. Some of the most affected pathways included glutathione metabolism, glutamate metabolism pathway, primary bile acid biosynthesis pathway, and sphingolipid metabolism pathway, which were all directed to the biological process of ferroptosis. Then, the main markers related to ferroptosis in the liver were examined, and the results demonstrated that the content of malondialdehyde was significantly increased, the activity of superoxide dismutase was significantly reduced, the ferroptosis inhibitory proteins GPX4 and System xc− were significantly downregulated, and the ferroptosis-promoting protein ACSL4 was significantly up-regulated. Judging from these results, we concluded that the mechanism of hepatotoxicity of Epimedium koreanum Nakai was probably related to the induction of ferroptosis in hepatocytes.